Spatial Variation of Tourist accommodation Serves (Hotels) in Iraq: with the exception of Kurdistan - Hadi, Safaqis Qasim (Al-Adab Journal, 2021)
Tourist residential services, namely hotels, are an important cornerstone in tourist attraction. That is because without them, tourist attractions lose much of their natural, religious,​ ​folkloric, and antique values and tourists fail to meet their trip goals. Hotels are the establishments that provide tourists with residence, food and other important services in hospitality industry. However, due to the development in tourist activities, the notion of hotel industry has developed to include communication, transportation, money exchanging, holding meetings, parties and carnivals, shopping centers, gyms, spa, and medical treatment, With the increase in oil revenues and political stability, tourist sector has developed in Iraq, especially in the 1980s, and culminated in building a number of important hotels in Baghdad. Yet, it suffered a dramatic decline because of the long war with Iran (1980-1988) and the severe​ economic sanctions following the Iraqi invasion of Kuwait in 1990. After 2003, Iraqi tourist sector has undergone a period of immerse growth due to the diversity in Iraqi climate, geography and tourist and environmental sites such as marshes, moors, valleys and mountains with their diverse human and animal life systems. Another aspect of Iraq tourist attraction is its famous religious sites such as the birthplaces and tombs of several prophets, like Ibrahim Abraham) in Ur,​ and​ the Shrines of Imams (grandsons of Prophet Mohammad) in Najaf, Karbala, Baghdad and Samara. Being the cradle of several civilizations, Iraq is replete with important sites in almost all its provinces such as Nasiriya, Babylon, Baghdad, Samara, Nineveh. The interest in visiting such huge reservoir of historical, cultural and religious sites has caused an increasing demand​ for hotels and hospitality services and activities. It has also placed provinces in ​certain categories; when referring to the interest in religious sites, Karbala comes first in hospitality services ​followed by Najaf and then Baghdad. But being the capital and, consequently, the residence of ​officials and diplomatic commissions, Baghdad holds the first rank in hotels classification.​The hotel sector suffers from several problems, whether in financial, organizational or planning terms by the concerned authorities. Many governorates have a distinct natural and cultural heritage in their folds, but they are not prepared for tourism activity despite the accession of some of these sites to the world heritage yard, as is the case in Babylon and the marshes of southern Iraq as well. Regarding the lack of interest in the rehabilitation and training of cadres specialized in the hotel activity.